A new composite consisting of Y zeolite and ZrO2 for fluid catalytic cracking reaction. (1st November 2020) - Liu, Wanrong; Liu, Xinmei; Gu, Yu; Liu, Yuxiang; Yu, Zhumo; Lyu, Yuchao; Tian, Yupeng
Abstract: In fluid catalytic cracking (FCC) unit, basic nitrogen species in heavy oil result in the poison of Y zeolite acid sites and the loss of heavy oil conversion. To solve this issue, Y/ZrO2 composites are prepared by a two-stage crystallization method. The composite bears a uniform particle size and micro-mesoporous hierarchical structure. The Zr–O–Si chemical bonds are observed between Y zeolite and ZrO2 in Y/ZrO2 composites, which result from the incorporation of Zr species into the framework of Y zeolite. Compared to the mechanical mixture of Y zeolite and ZrO2, composites have abundant Lewis acid sites, which capture basic nitrogen species to protect the acid sites over Y zeolite. It endows a higher heavy oil conversion (increased by 2 wt%) to the Y/ZrO2 composites in the catalytic cracking of heavy oil with high-basic nitrogen compounds. It is worth noting that the hierarchical pore structure of Y/ZrO2 composite inhibits coke deposition. These results are important to propose a new FCC catalyst to catalytic crack heavy oil with high amount of bulky basic nitrogen compounds. Graphical abstract: Image 1 Highlights: Y/ZrO2 composites consisting of Y zeolite and ZrO2 were prepared by a two-stage crystallization method. Y zeolite combined with ZrO2 via Zr–O–Si bonds in Y/ZrO2 composite. Y/ZrO2 composite shows excellent performance in catalytic cracking high-basic nitrogen feedstock.